2016
DOI: 10.15420/aer.2016:27:2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Tests in Atrial Fibrillation Ablation

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia observed in clinical practice, occurring in approximately 2 % of the general population.1-3 A progressive increase in both the prevalence and incidence of AF has been demonstrated in recent years, defining AF as a major economic and public health issue. 1 The identification of sites of AF initiation and/or maintenance within the pulmonary veins (PVs) has led to the development of percutaneous procedures to electrically isolate the PVs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 101 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…This is due to the developmental, anatomical, and electrophysiological differences between the LA and right atrium (RA) (Christoffels et al 2000;Mansour et al 2001). In addition, various ectopies originating from the LA, especially from the pulmonary veins or LA posterior wall, provide the induction mechanism of AF, and the action potential duration of the LA is shorter than that of the RA, facilitating the maintenance of the short wavelengths and micro-reentries (Qi et al 1994;Christoffels et al 2000;Aslanidi et al 2009;Gourraud et al 2016;Tutuianu et al 2016). Because of this, the main targets of radiofrequency AF catheter ablation are the pulmonary veins and LA posterior wall.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the developmental, anatomical, and electrophysiological differences between the LA and right atrium (RA) (Christoffels et al 2000;Mansour et al 2001). In addition, various ectopies originating from the LA, especially from the pulmonary veins or LA posterior wall, provide the induction mechanism of AF, and the action potential duration of the LA is shorter than that of the RA, facilitating the maintenance of the short wavelengths and micro-reentries (Qi et al 1994;Christoffels et al 2000;Aslanidi et al 2009;Gourraud et al 2016;Tutuianu et al 2016). Because of this, the main targets of radiofrequency AF catheter ablation are the pulmonary veins and LA posterior wall.…”
Section: Introductionmentioning
confidence: 99%
“…The complication rate per procedure ranged from 2.1% to 10.2% in the randomized trials with the exception of MacDonald et al . Most complications related to access site bleeding, and postprocedural infections.…”
Section: Safetymentioning
confidence: 95%
“…Large‐scale observational studies and multiple randomized controlled trials have demonstrated that catheter ablation is universally superior to AADs for the maintenance of sinus rhythm (66–89% for ablation vs. 9–58% for AADs), and improving AF‐related symptoms, exercise capacity, and quality of life . The contemporary AF ablation procedure is centered on circumferential ablative lesions that are placed within the left atrial myocardium just outside the tubular veins with an ultimate goal of electrical pulmonary vein isolation (i.e., bidirectional conduction block).…”
Section: Catheter Ablation Of Atrial Fibrillationmentioning
confidence: 99%
“…Anti-arrhythmic drug therapies are often ineffective in terminating AF or preventing a recurrence of AF, possibly because these drugs target a single pathophysiological mechanism. Invasive approaches, using catheter ablation of arrhythmogenic triggers, do not prevent the recurrence of AF, likely because of the persistence of arrhythmogenic substrates and non-pulmonary vein triggers [ 46 ]. In advanced forms of AF, abnormal atrial substrates, including Cx43, Cx40 and Cx45 abnormalities, are thought to act as drivers of arrhythmia perpetuation.…”
Section: Mechanisms and Factors Involved In The Development Of Vf mentioning
confidence: 99%